ISPAD Clinical Practice Consensus Guidelines 2022: Definition, epidemiology, and classification of diabetes in children and adolescents - Libman, Ingrid; Haynes, Aveni; Lyons, Sarah; Pradeep, Praveen; Rwagasor, Edson; Tung, Joanna Yuet‐ling; Jefferies, Craig A.; Oram, Richard A.; Dabelea, Dana; Craig, Maria E. (Pediatric diabetes, 2022)
A The possibility of other types of diabetes should be considered in the child who has negative diabetes-associated autoantibodies and: B an autosomal dominant family history of diabetes (maturity onset diabetes of the young [MODY]) age less than 12 months and especially in first 6 months of life (neonatal diabetes mellitus [NDM]) mild-fasting hyperglycemia (5.5–8.5 mmol/L [100–150 mg/dl]), especially if young, non-obese, and asymptomatic (MODY) a prolonged honeymoon period lasting more than 1 year or an unusually low requirement for insulin of ≤0.5 U/kg/day after 1 year of diabetes (MODY) associated conditions such as deafness, optic atrophy, or syndromic features (mitochondrial disease) a history of exposure to drugs known to be toxic to β-cells or cause insulin resistance (e.g., immunosuppressive drugs such as tacrolimus or cyclosporin; glucocorticoids or some antidepressants). Impaired insulin secretion and deficient insulin action may coexist in the same individual.2,3 While the etiology of diabetes is heterogeneous, most cases of diabetes can be classified into two broad etiopathogenetic categories (discussed later in further detail): T1D, characterized by the destruction of the ß-cells, usually by an autoimmune process, resulting in loss of endogenous insulin production, or T2D, characterized by the lack of an adequate insulin response in the presence of increasing insulin resistance. [...]it is now recognized that people with monogenic diabetes, an autosomal dominant diabetes pattern first termed MODY, may make up 1%–6% of autoantibody negative individuals who may, initially, be considered to have either T1D or T2D with decreased insulin secretion.6,7 DIAGNOSTIC CRITERIA FOR DIABETES IN CHILDHOOD AND ADOLESCENCE Diagnostic criteria for diabetes are based on BGL measurements and the presence or absence of symptoms.1–3 Different strategies can be used to measure BGL, including using a fasting plasma glucose (FPG) value, the 2-h plasma glucose (2-h PG) value during an OGTT, or hemoglobin A1c (HbA1c) criteria (Table 1) and in the absence of unequivocal hyperglycemia, diagnosis must be confirmed by repeat testing. HbA1c can be used as a diagnostic test for diabetes, in particular to test for prediabetes or T2D in youth4; providing that stringent quality assurance tests are in place and assays are standardized to criteria aligned to the international